Extra‐pair offspring are less heterozygous than within‐pair offspring in American redstarts Setophaga ruticilla. (22nd April 2019) - Hajdasz, Adrianne; McKellar, Ann E.; Ratcliffe, Laurene M.; Boag, Peter T.; Marra, Peter P.; Reudink, Matthew W.
Abstract : The vast majority of bird species are socially monogamous; however, extra‐pair paternity is nearly ubiquitous and a number of theories have been proposed to explain the prevalence of this mixed mating strategy. Here, we test the genetic compatibility hypothesis – the idea that females seek extra‐pair copulations with males whose genes are more compatible with her own. For this study, we examined eight years of paternity data (2004–2011) from a Nearctic‐Neotropical migratory bird, the American redstart Setophaga ruticilla, breeding in southeastern Ontario, Canada. We predicted that females paired with genetically similar males (higher relatedness) would be more likely to produce extra‐pair offspring and that extra‐pair offspring would have higher levels of heterozygosity than within‐pair offspring. Alternatively, because this population experiences high levels of immigration, females may produce extra‐pair offspring with more genetically similar males because of the potential for outbreeding depression. Using five highly variable microsatellite markers, we examined patterns of relatedness among social pairs as well as measures of offspring heterozygosity. In contrast to our predictions, we found no difference in relatedness between social pairs where the females produced extra‐pair offspring and social pairs where the females produced only within‐pair offspring. However, extra‐pair offspring were significantly less heterozygous than within‐pair offspring. Together, these findings suggest that females a) are not engaging in extra‐pair fertilizations based on relatedness to their social mate and b) appear to be mating with extra‐pair males that are more genetically similar to themselves. We suggest there may be benefits for females to mate with genetically similar extra‐pair males in highly outbred populations with high rates of immigration, such as for maintaining co‐adapted gene complexes or genes coding for local adaptations.